Soil yeasts, mycorrhizal fungi and biochar: their interactions and effect on wheat (Triticum aestivum L.) growth and nutrition - Moller, Leandra (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.